Topological origin of strain induced damage of multi-network elastomers by bond breaking. (October 2020) - Yin, Yikai; Bertin, Nicolas; Wang, Yanming; Bao, Zhenan; Cai, Wei
Abstract: Elastomers that can sustain large reversible strain are essential components for stretchable electronics. The stretchability and mechanical robustness of unfilled elastomers can be enhanced by introducing easier-to-break cross-links, e.g. through the multi-network structure, which also causes stress–strain hysteresis indicating strain-induced damage. However, it remains unclear whether cross-link breakage follows a predictable pattern that can be used to understand the damage evolution with strain. Using coarse-grained molecular dynamics and topology analyses of the polymer network, we find that bond-breaking events are controlled by the evolution of the global shortest path length between well-separated cross-links, which is both anisotropic and hysteretic with strain. These findings establish an explicit connection between the molecular structure and the macroscopic mechanical behavior of elastomers, thereby providing guidelines for designing mechanically robust soft materials.